Assessing of soil fertility using soil indices on different land used in Bintulu, Sarawak - Jamaluddin, Aiza Shaliha; Abdu, Arifin; Abdul Hamid, Hazandy; Jusop, Shamshuddin; Karam Singh, Daljit Singh; Karim, Md. Rezaul; Zulkeefli, Aizul Azfar (Faculty of Computer Science and Information Technology, Universiti Putra Malaysia, 2015)
Assessing land uses/land cover-induced changes in soil properties from natural forests to farmland are essential for addressing the issues of agricultural landscape sustainability. A study was conducted in the rehabilitated forest (RF), secondary forest (SF), oil palm (OP) and rubber plantation (RP) at Universiti Putra Malaysia Bintulu Campus, Sarawak in order to examine the soil fertility status using soil indices. Soils were sampled at two soil depths. The soil fertility status was evaluated using two indices, namely soil fertility index (SFI) and soil evaluation factor (SEF). The value of SFI was higher than SEF value for both depths. The highest SFI value was OP, followed by RP, RF and SF for the surface soil. The present study shows that soil fertility were affected by types of trees/different crops, soil managements, types of parent materials and climatic condition. Therefore, it is required to develop proper land use policy, sustainable soil management and cropping practices to combat the on ongoing soil degradation in the study area.